Oxidação enzimática de compostos fenólicos em água residuária do processamento do café - Torres, Juliana Arriel (2014)
Coffee is one of the agricultural products of great importance to Brazil, mainly to the state of Minas Gerais, and is undoubtedly of remarkable importance and expressiveness to their economy. The post-harvest processing of wet coffee consists in the use of a large amount of water throughout the process, resulting in a high-quality coffee, besides reducing costs and drying space. However, the resulting effluent is rich in inorganic and organic compounds, including phenolic compounds, which are highly toxic and some of them, when released into the environment, can accumulate in ground and surface water, as well as in the soil, in different food chains, being persistent in the environment and toxic to microorganisms in the biological treatment. Peroxidases are biocatalysts used in the removal of organic pollutants, with potential use in the treatment of effluents containing phenols. The objective of this study was to identify and quantify the phenolic compounds from coffee processing wastewater (CPW), evaluate different peroxidase sources in the oxidation of caffeic acid and in the oxidation of phenolic compounds from CPW, in the presence and absence of chemical additives. CPW presented a content of total phenolic compounds of 233.56 mg L-1 and caffeic acid was the major phenolic compound. Turnip peroxidase (TPE) proved efficient in the oxidation of caffeic acid, reaching a percentage of 51.05% in only 15 minutes of reaction. Nevertheless, the efﬁciency of this catalyst showed dependent on pH, H2O2 concentrations and enzyme used. The highest percentage of oxidation was obtained at pH 8, in a molar ratio caffeic acid:H2O2 of 1:7, and using an enzyme concentration of 14.43 U mL-1. TPE presented an oxidation potential of caffeic acid (75.99% ± 0.48) higher than the peroxidase extracted from the soybean hulls (SHP) and the commercial enzymes horseradish peroxidase (HPR) and soybean peroxidase (CSP). However, in the oxidation of CPW, HPR was more efficient, with 74.37% ± 0.16 oxidation, followed by TPE, with 67.59% ± 0.11. There was no influence on the oxidation of CPW by SHP in the presence of polyethylene glycol and Triton X-100. The high content of phenolic compounds found in CPW justifies the need for a treatment of this effluent before its discharge into receiving water bodies, or even before being subjected to other types of treatments. The proposed treatment can be effective in the oxidation of phenolic compounds in CPW and may be associated with conventional biological treatment processes.